Interpersonal Communication Patterns of Lupus Patients at Cinta Kupu Community - Hartono, Anisya Hafila; Kurniawati, Dewi; Mazdalifah, Mazdalifah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the interpersonal communication patterns of lupus sufferers in the North Sumatra Cinta Kupu community, focusing on self-disclosure, initial diagnosis, and self-concept. Using a qualitative, phenomenological approach, the research seeks to understand the experiences of six informants, divided into key and triangulation groups. Data collection involved interviews and observations. The findings reveal that interpersonal communication patterns are influenced by internal factors, such as the desire to survive, communicate, and fulfill social needs, as well as external factors like empathy, motivation, and self-proving. Self-disclosure, shaped by self-acceptance, also impacts various aspects of their lives within the community. The desire to continue offspring, fulfill the needs of life as social beings, the desire to survive, and the desire and need to communicate with others. While external factors are: empathy, motivation (support) and imitation and self-proof.